Nationwide survey for primary sclerosing cholangitis and IgG4-related sclerosing cholangitis in Japan - Tanaka, Atsushi; Tazuma, Susumu; Okazaki, Kazuichi; Tsubouchi, Hirohito; Inui, Kazuo; Takikawa, Hajime (Journal of hepato-biliary-pancreatic sciences, 2014)
Background We previously conducted nationwide surveys for primary sclerosing cholangitis (PSC) in Japan, and demonstrated several characteristic features of Japanese PSC patients, yet patients with IgG4‐related sclerosing cholangitis (IgG4‐SC) might be misdiagnosed as PSC. Since the clinical diagnostic criteria of IgG4‐SC were established in 2012, we again conducted a nationwide survey to investigate the characteristics of PSC and IgG4‐SC lacking pancreatic involvement. Methods The design was a questionnaire‐based, multi‐center retrospective study. The enrolled subjects were patients with PSC and IgG4‐SC without pancreatic involvement diagnosed after 2005. Results We enrolled 197 PSC and 43 IgG4‐SC patients without pancreatic lesions. The male dominance was significantly evident in IgG4‐SC (P = 0.006). In patients with PSC, two peaks in age distribution were clearly observed. IgG4‐SC was not detected in any patient younger than 45 years of age. At presentation, serum albumin and IgM were significantly higher in PSC, while serum IgG and IgG4 were significantly elevated in IgG4‐SC. Inflammatory bowel disease (IBD) was detected in only 68/197 PSC patients (34%). The prognosis of IgG4‐SC was considerably better than that of PSC. Conclusion We confirmed several interesting clinical details of PSC in Japanese patients: two peaks in the age distribution and lower prevalence of IBD.